2023
DOI: 10.3389/phrs.2023.1605474
|View full text |Cite
|
Sign up to set email alerts
|

An Umbrella Review of the Best and Most Up-to-Date Evidence on the Built Environment and Physical Activity in Older Adults ≥60 Years

Abstract: Objectives: To present the best and most up-to-date evidence on associations between built environment (BE) attributes and overall and specific domains of physical activity (PA) (i.e., leisure, transport, walking, and cycling) in older adults (≥60 years).Methods: An umbrella review was undertaken to compile evidence from systematic reviews using the Joanna Briggs Institute methodology. A comprehensive search (updated 16 August 2022), inclusion/exclusion of articles via title/abstract and full-text reviews, dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…While there were many similarities between this lower-income, insufficiently active aging population and those that have been studied previously, several domains of NEWS-A-such as traffic, crime, and hazards that other studies have found to be important-were not included in the final regression models in this investigation due to lack of significance [22,[62][63][64]. Comparing the findings of our study with those of other researchers elucidates that perceptions of aesthetics and street connectivity seem to be similarly important to PA in this specific insufficiently active midlife and older adult population as well as in the general aging population [62,63,65].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…While there were many similarities between this lower-income, insufficiently active aging population and those that have been studied previously, several domains of NEWS-A-such as traffic, crime, and hazards that other studies have found to be important-were not included in the final regression models in this investigation due to lack of significance [22,[62][63][64]. Comparing the findings of our study with those of other researchers elucidates that perceptions of aesthetics and street connectivity seem to be similarly important to PA in this specific insufficiently active midlife and older adult population as well as in the general aging population [62,63,65].…”
Section: Discussionmentioning
confidence: 97%
“…Individual perceptions of the built environment, as measured primarily by NEWS-A or its full-length precursor, NEWS, have consistently shown associations with PA outcomes [59]. For example, a recent meta-analysis by Stearns et al (2023) reported significant positive associations between total PA and total walking with greenery and aesthetically pleasing scenery, as well as a positive association between street connectivity and walking for transportation [22]. Both quantitative and qualitative studies have also indicated the importance of aesthetic components such as shady trees and the presence of attractive features in facilitating PA behaviors, especially for older adults [28,60].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Walking, cycling, and wheeling are among the most popular forms of PA [13], and heavily rely on supportive pedestrian streetscapes [4,21,22]. As weather and climate conditions change, and to mitigate further climate changes through promotion of active transportation modes like walking, it is increasingly important for urban design and planning to consider impact of weather on pedestrians.…”
Section: Introductionmentioning
confidence: 99%